Assessing the Potential of Biomass Power Generation for Renewable Energy Transition in South Papua Province, Indonesia - Martoyoedo, Satryo; Uyun, Aep Saepul; Nur, Syukri Muhammad; Mikail, Barry (MSD Institute, 2024)
This study aims to explore the potential for biomass-based power plant to accelerate the development of renewable energy to replace the role of fossil energy in Merauke district, South Papua Province. The method used in this study is, first, to collect data and analyze the load on the grid system and the portion of the energy mix as well as the availability of woody biomass from forest areas by making a simulation of the development of a 2 x 12 MW Biomass Power Plant. Second, by conducting experiments to obtain woodchip conversion, as the fuel of the Biomass Power Plant, from the wood log and conversion from Biomass Power Plant capacity to the required biomass plantation area. The results provide an overview of the big potency for developing biomass-based power generation by utilizing biomass from the local industrial plantation forest and show the energy transition towards energy independence. This study can be useful for policy makers and opportunities for entrepreneurs or suppliers of wood biomass, as well. For the future, in terms of fuel efficiency, it is necessary to reduce the plantation area as a source of biomass for power plants by reducing the moisture content of the woodchip to increase the calorific value and utilizing the forest residue. Furthermore, the comparison cost study between fossil power plant and biomass power plant, as well as the strategy for preserving the plantation to ensure a steady biomass supply is conducted.